Pengaruh Getah Jarak Pagar (Jatropha curcas L) Terhadap Penyembuhan Luka Pada Tikus (Rattus norvegcus) Strain Wistar (In Vivo) - Ridha, Dzu Asfiatun, drg. Mahmud Kholifa, MDSc, drg. Retno Sari (2016)
Injuries could occur because of various things, such as exposed sharp objects, exposed to medical equipment, operator actions during treatment, blow hard objects and accidents. The body could give damage respond to the body form defence for the wound healing process. Wound healing could be seen clinically, the wound usually heal within two weeks but the wound heal more slowly if the wound was large enough and deep. Many drugs could heal wounds, but had an expensive pricerelatively, had side effects and difficult to find, one of them was oxoferin. The sap of Jatropha (Jatrophacurcas l.) was one of the herbs that had active substances which were numerous and could help accelerate the process of wound healing in the neck area of exstra-oral (Rattusnorvegicus) rats. The researched by the sap of jatropha had the objective to accelerate the process of wound healing clinically in the neck area of rats. This type of research was purely experimental design laboratory used posttest only controlgroup design. The researched method was to measure the diameter of the wound and the healing by using a sample of 27 rats were divided into three treatments groups, named the sap of jatropha, oxoferin and distilled water. The Injury was done by using a 3 mm punch biopsy, then measured on days 4, 7 and 10 used a caliper. The measurements were analyzed using two-way ANOVA and LSD The results showed the average diameter of the wound by using jatropha on day 10 of 0.36 mm, oxoferin of 1.00 mm, and 1.34 mm of distilled water, the results could be seen that the latex of Jatropha could help speed up the healing of wounds compared with oxoferin and distilled water. ANOVA test results conducted two channels, named p = 0.000 (P <0.05) and the Post Hoc LSD test showed a value of p <0.05 so that it could be concluded that the sap of Jatropha (Jatrophacurcas l.)had effect on wound healing in rats Rattusnorvegicuswistar strain. Keywords: Wound, wound healing, latex of Jatropha, the diameter of wound, Rattus norvegicus